Kajian Kebutuhan Sarana Perlintasan Warga Desa Liang Dan Neath Pada Sungai Nalbessy Kabupaten Buru Selatan - Hamkah Hamkah; Lenora Leuhery; Gunawan Abdullah (Journal of Applied Civil Engineering and Infrastructure Technology, 2020)
The social media coverage entitled 75 Years of Indonesia Independence day but we are not yet free shown South Buru hinterland people activities as crossing the Nalbessy river. The safety of user facilities stakes because of breaking up risk, and have fatal consequences washed away by the river current swift. Electronic and print media's rise motivated to examine South Buru hinterland people's facilities need to cross the river. The study aims to trace activities crossing locations and analyzing user potential based on population data. We Presenting roads and bridges history around Liang and Neath Villages in a strip map handling the Namrole - Leksula segment. The method uses Google Earth, structured, and systematic study stages sourced from secondary data. The study results showed that the Nalbessy River coordinate of -3.7628° S and 126.5444° E is Wai Nalbessy III bridge's construction planned location. The Namrole – Leksula segment crosses two villages in South Buru (Liang and Neath). In handling roads until 2019, pavement conditions are still not uniform, consisting of 3 types: Hotmix 7.0 Km, Optional Stockpile of 4.0 Km, and Dirt Road 42.0 Km. The handling of provincial roads has built three bridges out of the 33 bridges plan. Estimated construction cost, the implementation time of the 50 m bridge span Wai Nalbessy III, according to the type of construction, respectively: Rp. 4 billion, four months a symmetrical pedestrian suspension bridge, Rp. 15 billion, ten months of steel frame, and Rp. 20 M, 1 Year for T beam concrete bridge.